2019
DOI: 10.1002/pssa.201800999
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Sensing Performance of Surface‐Activated MoS2 Nanosheets Made by Hydrothermal Method with Excess Sulfur Precursor

Abstract: Defect engineering of two‐dimensional (2D) nanostructures is of significant importance for achieving enhanced surface properties in optoelectronic, sensors, and catalytic applications. In this work, the authors study the gas‐sensing properties of 2D molybdenum sulfide (MoS2) nanosheets fabricated using a hydrothermal synthetic route with various nominal S/Mo precursor ratios, in order to generate nano‐domains on the surface. The effect of the excess S precursor on the morphology and the resulting gas sensing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…17,37 However, some other works indicated that in spite of slow rates of gas adsorption and desorption, the pristine MoS 2 -based sensors showed the complete recovery at RT to target gases. 20,[38][39][40] This characteristic can be attributed to several factors, such as high specic surface area, defective/strained surface and weak van der Waals binding between the target gas and the MoS 2 surface. 20,38,39 In addition, Ikram et al indicated that the high specic surface area not only increases the response of the sensor but also plays an important role in fast response and recovery times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…17,37 However, some other works indicated that in spite of slow rates of gas adsorption and desorption, the pristine MoS 2 -based sensors showed the complete recovery at RT to target gases. 20,[38][39][40] This characteristic can be attributed to several factors, such as high specic surface area, defective/strained surface and weak van der Waals binding between the target gas and the MoS 2 surface. 20,38,39 In addition, Ikram et al indicated that the high specic surface area not only increases the response of the sensor but also plays an important role in fast response and recovery times.…”
Section: Resultsmentioning
confidence: 99%
“…20,[38][39][40] This characteristic can be attributed to several factors, such as high specic surface area, defective/strained surface and weak van der Waals binding between the target gas and the MoS 2 surface. 20,38,39 In addition, Ikram et al indicated that the high specic surface area not only increases the response of the sensor but also plays an important role in fast response and recovery times. 41 Thus, understanding the detailed mechanism for the complete recovery of the sensor is still under debate because of the combined effects of physi-, chemi-sorption, role of defects sites and transduction mechanism 37 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the three-dimensional (3D) assembly of multilayer TMD nanosheets has attracted the attention of many researchers, since the gas adsorption at the edge sites of the TMD nanosheets is more significant than at their basal plane, thus enhancing sensitivity and selectivity. 26–28 In the case of MoS 2 , its basal plane is most of the times used as a chemical receptor, because it is easy to expose and produce using exfoliation or chemical vapor deposition techniques. However, this basal plane surface has minimal dangling bonds, and due to thermodynamic forces, it is difficult to expose their edge sites to the environment.…”
Section: Introductionmentioning
confidence: 99%